PENERAPAN METODE FONIK DALAM MENGATASI KESULITAN MEMBACA PADA SISWA KELAS III SD DI UPT SDN 20 TURATEA KABUPATEN JENEPONTO - Fadhila Amalia Pertiwi; Munirah; Ummu Khaltsum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the phonics method in overcoming reading difficulties among third-grade students at UPT SDN 20 Turatea, Jeneponto Regency. This study employed a descriptive qualitative approach. The subjects of this research were the teacher and third-grade students. Data were collected through observation, interviews, and documentation, and then analyzed using data reduction, data display, and conclusion drawing. The results showed that the implementation of the phonics method was carried out systematically through several stages, including introducing letter sounds, blending sounds into syllables, and segmenting words into individual sounds, supported by the use of letter cards and picture cards. The application of this method had a positive impact on students’ reading abilities, as indicated by improvements in recognizing letter sounds, reading syllables, and reading simple words. In addition, students’ motivation and confidence in reading also increased. However, some difficulties were still found, such as students’ inability to distinguish similar letters (b–d and p–q), reading that was still hesitant, and limitations in reading simple sentences and reading comprehension. Therefore, more varied learning strategies and continuous guidance are needed to further improve students’ reading abilities.